Towards a taxonomy of cache-based transport protocols in wireless sensor networks - Alipio, Melchizedek I. (Animo Repository, 2017)
Sensor nodes in Wireless Sensor Networks (WSNs) are battery-powered devices that consume energy during data transmission and processing. One of the most critical tasks in a sensor network is to deal with optimizing the power consumption. One possible way to minimize this problem is caching the data. Data caching is a promising technique for improving the performance of transport protocols in terms of reliability in most sensor applications. Since, a typical data transmission consumes more energy than processing in a sensor network, the use of caching enables quick access to data. Therefore, caching, if used efficiently, could reduce overall network traffic and hence bandwidth can be optimally utilized. Unfortunately, a systematic treatment of caching in WSNs was until now lacking. Given that WSNs are expected to play an important role in Internet of Things (IoT) and wireless sensing applications, the authors believed that now is time to collect the results of years of research on this important topic. This paper presents a thematic taxonomy of the current cache management mechanisms of transport protocols in wireless sensor networks. The similarities and differences of the transport protocols based on the important parameters, such as cache insertion/replacement policy, cache size requirement, cache location, cache partition, and cache decision are investigated in this paper. In addition to that, we discuss open research issues and challenges of implementing intermediate caching to various sensor deployment. In the future, this study can be a basis so that future implementations can choose the combination of caching mechanisms that best fits their target in the field of instrumentation and measurements, especially in WSN applications.